2020
DOI: 10.1111/eci.13458
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose methylprednisolone in nonintubated patients with severe COVID‐19 pneumonia

Abstract: Background Recent trials with dexamethasone and hydrocortisone have demonstrated benefit in patients with coronavirus disease 2019 (COVID‐19). Data on methylprednisolone are limited. Methods Retrospective cohort of consecutive adults with severe COVID‐19 pneumonia on high‐flow oxygen (FiO2 ≥ 50%) admitted to an academic centre in New York, from 1 March to 15 April 2020. We used inverse probability of treatment weights to estimate the effect of methylprednisolone on clinical outcomes and intensive care resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 32 publications
4
74
0
5
Order By: Relevance
“…In a single-centre, real-life population receiving the same standard of care, our findings confirmed the efficacy of corticosteroids in reducing the risk of mechanical ventilation or death in patients with moderate to severe COVID-19 pneumonia. These results were in line with those of previous cohort studies [ 9 , 10 , 17 , 18 ] and a large randomized trial [ 11 ] where corticosteroids were included in the standard of care for COVID-19 pneumonia. Corticosteroid therapy was also beneficial in older and comorbid patients who were not eligible for intensive care.…”
Section: Discussionsupporting
confidence: 91%
“…In a single-centre, real-life population receiving the same standard of care, our findings confirmed the efficacy of corticosteroids in reducing the risk of mechanical ventilation or death in patients with moderate to severe COVID-19 pneumonia. These results were in line with those of previous cohort studies [ 9 , 10 , 17 , 18 ] and a large randomized trial [ 11 ] where corticosteroids were included in the standard of care for COVID-19 pneumonia. Corticosteroid therapy was also beneficial in older and comorbid patients who were not eligible for intensive care.…”
Section: Discussionsupporting
confidence: 91%
“…Since there had been con icting results in other viral pneumonia regarding the safety and bene cial effects of corticosteroids, the world health organization (WHO) in the early period of the pandemic published recommendations against the routine use of these agents in managing patients with COVID-19 (26). However, it is well known that glucocorticoid agents are thought to be useful in stopping the in ammatory storm by suppressing pro-in ammatory gene expression and decreasing cytokine levels if used at the appropriate time in the disease course (34).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, methylprednisolone achieves higher lung tissue-to-plasma ratios in animal models than dexamethasone, which may thus be more effective for lung injury (24). Also, previous studies have shown the effectiveness of methylprednisolone on treating SARS disease (25,26). Hence, we hypothesized that methylprednisolone could be more effective than other corticosteroids, particularly dexamethasone.…”
Section: Introductionmentioning
confidence: 98%
“…In an early study, all hospitalized COVID-19 patients had pneumonia confirmed by chest CT. [ 7 ]. In large study, 48.8% of hospitalized patients had severe pneumonia requiring high-flow O 2 therapy [ 8 ]. Adults admitted to emergency departments with suspected COVID-19 that were subsequently confirmed were more than twice as likely to die or receive organ support as those who did not have COVID-19 confirmed, despite having similar age and comorbidities (expect chronic lung disease) [ 9 ].…”
Section: Major Covid-related Pulmonary and Cardiovascular Injuriesmentioning
confidence: 99%